PERKEMBANGAN MODEL PENELITIAN KEPATUHAN PAJAK - Nur Cahyonowati; Darsono Darsono (SIMAK, 2018)
This article provides a review of the theories that are widely used in the study oftax compliance behavior on individual taxpayers. Tax compliance research startsfrom a traditional model that assumes taxpayer as a rational individual whomaximizes utility under conditions of uncertainty. This traditional model ignoresthe psychological aspect of human behavior. Tax compliance studies also raisepsychological issues such as justice, tax norms. The development of the taxcompliance model further integrates economic and psychological factors in taxcompliance decision making.